Extraction of Flavonoid Content from Banana Peel (Musa Paradisiaca L.) by Ultrasound – Assisted Extraction Method and Its SPF Value - Putri, Hasna Nabila; Budi Nursanto, Eduardus; Floresyona, Dita; Ayoub, Muhammad; Yusouf, Mohd Hizami Mohd (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2023)
In this study, banana peel was used as a natural sunscreen compound because of its natural antioxidants, such as flavonoids, tannins, triterpenoids, and phenols. Extraction is carried out using Ultrasound-Assisted Extraction method with variations in ethanol solvent concentration and material to solvent ratio at 45oC for 45 minutes. The ethanol concentrations used are 96%, 70%, and 50% and the material to solvent ratio 1/10, 1/20, and 1/30. From the results of the study, the highest yield and SPF value were obtained at ethanol concentration of 50% and material to solvent ratio 1/30. The yield in this variation is 15.2646%, and the SPF value is 8.9874 with the maximum protection category. The highest Total Flavonoid Content (TFC) results was obtained at 70% ethanol concentration and the ratio of material to solvent 1/30, namely 1.6559 mg QE/g. From the variation with the best TFC value, the mass transfer coefficient is 0.0151 mL/µg QE.min.